Sweden : Financial Sector Assessment Program-Technical Note-Regulation and Supervision of Cross-Border Securities Activities. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for Sweden in the areas of regulation and supervision of cross-border securities activities. The Finansinspektionen (Financial Supervisory Authority, FI) should review the consumer protection area's activities to assess where the current consumer protection focus should be complemented with explicit consideration of financial stability risks. Improvements in data availability and better analysis tools would improve the FI's ability to analyze risks and plan its supervisory activities. Enhancements to cross-border supervisory cooperation and active participation in the work of the European Securities and Markets Authority are also necessary complements to the FI's current active domestic supervisory program.